2017
DOI: 10.1002/cbin.10770
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA: an important regulator in acute myeloid leukemia

Abstract: MicroRNAs (miRNAs) are a general class of endogenous non-coding RNAs with a length of 22 nucleotides, widely existing in diverse species and playing important roles in malignancies initiation and progression. MiRNAs are essential to many in vivo biological processes such as cell proliferation, apoptosis, immune response, and tumorigenesis. Significant progress till date has been made in understanding the roles of microRNAs in normal hematopoiesis and hematopoietic malignant diseases. In this review, we summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…miRNAs are a general class of endogenous noncoding RNAs of 22–25 nucleotides, widely existing in diverse species, and playing essential roles in cell proliferation, immune response, and maintaining homeostasis . miRNAs can control the expression of nearly 30% of protein‐coding genes by targeting a sequence located in the 3′‐untranslated region (3′‐UTR) of the target genes, resulting in cleavage or inhibition of translation and causing profound changes in protein levels . Moreover, a single miRNA can simultaneously regulate multiple target genes within a genetic network, resulting in potent cumulative effects on gene networks and affect many biological processes and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a general class of endogenous noncoding RNAs of 22–25 nucleotides, widely existing in diverse species, and playing essential roles in cell proliferation, immune response, and maintaining homeostasis . miRNAs can control the expression of nearly 30% of protein‐coding genes by targeting a sequence located in the 3′‐untranslated region (3′‐UTR) of the target genes, resulting in cleavage or inhibition of translation and causing profound changes in protein levels . Moreover, a single miRNA can simultaneously regulate multiple target genes within a genetic network, resulting in potent cumulative effects on gene networks and affect many biological processes and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome translocations leading to fusion genes such as MLL-AF9 , PML-RARα , and AML1-ETO as well as various genetic mutations such as FLT3 , Kit , TET2 , and IDH1 contribute to the pathogenesis of AML [ 3 ]. However, recently emerging discoveries have indicated that epigenetic dysregulations including DNA hypermethylation and non-coding RNAs such as miRNAs play an important role in the pathogenesis of AML [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a general class of endogenous non-coding RNAs that are 22 nucleotides long, are found in diverse species and play important roles in the initiation and progression of malignancies. miRNAs are essential to many in vivo biological processes, such as cell proliferation, apoptosis, the immune response and tumorigenesis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%